ROMANTICISM IN THE POEM “ILA UMMI” BY MAHMOUD DARWISH BASED ON THE PERSPECTIVE OF JOHANN WOLFGANG VON GOETHE - Mohammad Ulil Albab Abdalah; Respati Yurisa, Penny (Lire Journal (Journal of Linguistics and Literature), 2025)
This paper?uses Johann Wolfgang von Goethe's literary Romanticism to analyze traits of Romanticism in Mahmoud Darwish's "Ilaa Ummi." It examines how aspects of Goethean Romanticism?including emotional expression, attitude toward nature, and spiritual importance are present in the poem. The research identifies a knowledge gap in literary studies by analyzing Goethean Romanticism in a contemporary Arabic literature context, which has been looked at through a political or?identity lens, and not a Romantic one. Through close reading and thematic analysis, the study uses a descriptive qualitative method to explore how certain hallmarks of Goethean Romanticism, such as subjectivity,?reverence for nature, and quest for spiritual meaning, can be found in Darwish's oeuvre. The findings highlight three major categories: (1)?pathos, represented by mother-longing and love for the mother, (2) the human-nature relationship, where landscapes denote warmth and emotional bond, and (3) deeper spiritual embodiment, which articulates existential contemplation and personal identity exploration. In a way, by tracing the tints and?shades of Darwish’s oeuvre, the work attends to the reductiveness of denoting the poet as “postmodern” (which had fallen out of fashion by the time he had died) and highlights Goethean Romantic elements to his literary agenda, bridging disparate Eastern and Western traditions. The study sheds light on the relevance of?Goethean Romanticism in non-Western poetry and advances the research into intertextual connections between Eastern and Western literatures.